Significance of bleeding control in hemorrhagic cyst infection in autosomal dominant polycystic kidney disease: a case presentation with literature review - Shunsuke Takayanagi; Keita P. Mori; Shigeto Kubo; Natsumi Mishima; Tomoka Watanabe; Mea Asou; Misaki Taniguchi; Miho Miyauchi; Yoshiaki Higashi; Takaya Handa; Tomomi Endo; Takeshi Matsubara; et al. (Renal Replacement Therapy)
Abstract Background In patients with autosomal dominant polycystic kidney disease (ADPKD), renal and hepatic cystic infections are common complications, sometimes frequent and refractory. Hemorrhagic complications are often present in these cases. Owing to the diversity of patient backgrounds, the treatment of these complications has not been standardized. Here we report three cases that suggest the significance of detecting and treating hemorrhagic complications in cases of cyst infection. Case presentation Case 1: A 46-year-old man on low-dose aspirin for antiphospholipid antibody syndrome presented with fever, left flank pain, and gross hematuria. He had a history of frequent renal cyst infections. Imaging studies revealed a hemorrhagic cyst infection of the left kidney and acute kidney injury. He was treated with ciprofloxacin and tranexamic acid, and aspirin was discontinued. Subsequently, infection and bleeding successfully improved after treatment for 2 months. To date, cyst infection has not recurred. Case 2: A 70-year-old man on eicosapentaenoic acid for dyslipidemia presented with fever and left flank pain which was diagnosed as a hemorrhagic cyst infection of the left kidney. He had a history of renal cyst infection. Hemorrhagic cyst infection of the left kidney was made with imaging studies and positive blood cultures. Ciprofloxacin and metronidazole were administered, and eicosapentaenoic acid was discontinued. The infection and bleeding resolved after treatment for 1 month. To date, cyst infection has not recurred. Case 3: A 63-year-old man on chronic maintenance hemodialysis receiving warfarin for atrial fibrillation and cardiogenic cerebral embolism presented with fever, back pain, and hypotension. On magnetic resonance imaging (MRI) and computerized tomography (CT), he was diagnosed with hemorrhagic cyst infection of the liver. Despite multidrug antibiotic therapy and discontinuation of warfarin, the bleeding tendency did not improve, and he died after 3 months. Conclusions Since cyst hemorrhage might be an aggravating complication in the treatment of refractory and recurrent cyst infections in patients with ADPKD, we believe that a careful imaging evaluation should be performed to detect cyst hemorrhage in these cases.